Analisis Faktor-Faktor yang Mempengaruhi Loyalitas Karyawan pada Pertokoan di Sepanjang Jalan Malioboro Yogyakarta. - Suhartini, Yati (Universitas PGRI Yogyakarta, 2017)
The research was carried out to know the influence of career development, compensation and job characteristics to employee loyalty at stores along Malioboro street, Yogyakarta.The population of the research were all of Sales Promotion Girls (SPG) and Sales Promotion Boys (SPB) working at stores along Malioboro street. Samples were taken with non-probability sampling technique by quota sampling, as many as 100 respondents. The data was collected by applying questionnaires, and analyzed by using multiple linear regressions with the help of SPSS program for windows release 16.0.This research concluded that factors of career development, compensation and job characteristics, partially or simultaneously showed a positive and significant influence to employee loyalty. These were indicated by the regression coefficient value of each factor of career development, compensation and job characteristics to employee loyalty were 0.421 (X1); 0.149 (X2); 0.411 (X3); and the significant level of each factor were 0.000; 0.45 and 0.000, respectively. While the value of F amounting to 51.235 with the sign.ificance level of 0.000; whereas adjusted R square equal to 0.604.